Electromagnetic Interference Impact of Wireless Power Transfer System on Data Wireless Channel - Elena, Baikova (2018)
This paper focuses on measurement and analysis of the electromagnetic fields generated by wireless power transfer system and their possible interaction on data transmission channel. To measure the levels of electromagnetic fields and spectrum near the wireless power transfer equipment the measurement system in the frequency range 100 kHz to 3 GHz was used. Due to the advances in technology it becomes feasible to apply the wireless power transfer in the electric vehicles charging. Currently, in the Faculty of Science and Technology of the University Nova high power wireless power transfer systems are in development. Those systems need to be controlled by several microcontrollers in order to optimize the energy transmission. Their mutual communication is of extreme importance especially when high intensity fields will generate highly undesired influence. The controllers are supposed to communicate with each other through radio frequency data channels. The wireless power transfer system with the electromagnetic interference may influence or completely disrupt the communication which will be a severe problem.